The Effect of Project-Based Learning Implementation with Photonovel Media on Science Process Skill and Critical Thinking Ability of the IV Grade Students at SDN Wirowongso 01 - Shinta Fibriantie; Sukidin Sukidin; Suparti Suparti (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
The IV grade students of SDN Wirowongso 01 are less motivated to follow the learning since assuming that it is complicated and less attractive. Based on the teacher's analysis, it is known that the student's achievement in following the learning was not maximum, in which 6 students got 50; 3 students got 60; 15 students got 70; 3 students got 80, and 2 students got 90 from the total 29 students. Based on the data, the researcher implemented project-based learning combined with photonovel to make the learning more exciting and meaningful. So, there was an improvement in the students' science process skills and critical thinking ability. The data collection procedures used were test and non-test. The data were the result of pretest and post-tests carried out by the students in the experimental and control classes. It can be seen from the pretest data that there was an improvement. However, through more profound analysis, the control class with conventional learning had never shown optimum improvement. Then, the N-Gain relative effectiveness calculation on pretest and post-test in both classes showed an improvement. Nevertheless, for the control class, the calculation result showed 0.23810 or in the lowest range. Meanwhile, the experimental class obtained 0.58696 or moderate category, in which the N Gained for the combination showed 2.456>1. This means that the implementation of project-based learning with photonovel to 29 students in the experimental class was more effective than conventional learning in the control class.